2020
DOI: 10.1210/jendso/bvaa046.1590
|View full text |Cite
|
Sign up to set email alerts
|

SAT-158 New Data on High Prevalence and Time of Occurrence of New Onset Hypothyroidism Associated with Mitotane Therapy in a Cohort of Adrenocortical Cancer

Abstract: Context. Mitotane is a steroidogenesis inhibitor and an adrenocorticolytic drug used to treat adrenocortical cancer (ACC). Central hypothyroidism is recognized in mitotane-treated patients and recent data suggested that mitotane could have an inhibitory effect on TSH-secreting cells in the pituitary gland. Moreover, mitotane may lead to induction of thyroid hormone metabolism. Clinical data on hypothyroidism related to mitotane such as prevalence and time of occurrence was described in a limited number of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These results were expected, as central hypothyroidism has been recognised as a side effect of mitotane therapy, meaning that whilst the TSH concentration may appear within the reference range, the fT4 concentrations are generally low. Poirier ( 14 ) concluded that induction of mitotane therapy had been associated with a central hypothyroidism prevalence of 73.3%. This accentuates the importance of regular thyroid function investigations to assess individuals’ needs for levothyroxine therapy ( 7 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were expected, as central hypothyroidism has been recognised as a side effect of mitotane therapy, meaning that whilst the TSH concentration may appear within the reference range, the fT4 concentrations are generally low. Poirier ( 14 ) concluded that induction of mitotane therapy had been associated with a central hypothyroidism prevalence of 73.3%. This accentuates the importance of regular thyroid function investigations to assess individuals’ needs for levothyroxine therapy ( 7 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poirier ( 14 ) concluded that induction of mitotane therapy had been associated with a central hypothyroidism prevalence of 73.3%. This accentuates the importance of regular thyroid function investigations to assess individuals’ needs for levothyroxine therapy ( 7 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation